2020
DOI: 10.3390/agronomy10020313
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Female Panicles Reveals Gene Expression Responses to Drought Stress in Maize (Zea mays L.)

Abstract: Female panicles (FPs) play an important role in the formation of yields in maize. From 40 days after sowing to the tasseling stage for summer maize, FPs are developing and sensitive to drought. However, it remains unclear how FPs respond to drought stress during FP development. In this study, FP differentiation was observed at 20 and 30 days after drought (DAD) and agronomic trait changes of maize ears were determined across three treatments, including well-watered (CK), light drought (LD), and moderate drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…KEGG pathway analysis showed that “biosynthesis of other secondary metabolites” and “carbohydrate metabolism” were involved in response to low drought stress, whereas “starch and sucrose metabolism” and “plant hormone signal transduction” played important roles in medium drought response. Notably, three genes, cuc2 (LOC103629107), TE1 (LOC541683), and DLF1 (LOC100037791), emerged as significant players in silk differentiation under drought stress conditions …”
Section: Uncovering Role Of Transcriptomics For Drought and Heat Tole...mentioning
confidence: 99%
See 2 more Smart Citations
“…KEGG pathway analysis showed that “biosynthesis of other secondary metabolites” and “carbohydrate metabolism” were involved in response to low drought stress, whereas “starch and sucrose metabolism” and “plant hormone signal transduction” played important roles in medium drought response. Notably, three genes, cuc2 (LOC103629107), TE1 (LOC541683), and DLF1 (LOC100037791), emerged as significant players in silk differentiation under drought stress conditions …”
Section: Uncovering Role Of Transcriptomics For Drought and Heat Tole...mentioning
confidence: 99%
“…Notably, three genes, cuc2 (LOC103629107), TE1 (LOC541683), and DLF1 (LOC100037791), emerged as significant players in silk differentiation under drought stress conditions. 124 Similarly, transcriptome interplay during kernel formation from flag leaf and developing kernels observed downregulation of genes corresponding to cell division, formation of anatomical boundaries, and nucleosome assembly alongside genes regulating histone proteins. Cell division was significantly reduced due to downregulation of its corresponding genes, i.e., CYC1;2, CYC2;3, CYC3;1, and CYC3;4 and auxins were most affected plant hormone as indicated by differential expression of auxin responsive genes, i.e., IAA3, IAA7, IAA8, IAA13, IAA26, ARF1, ARF3, ARF6, ARF11, and IBR1.…”
Section: Transcriptomic Insights Into Drought Tolerance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The irruption of transcriptomics, metabolomics, high-throughput DNA sequencing and high-density microarrays in the analysis of plants' responses to stress have brought new insights and allowed a better understanding on plants reactions to stressful conditions [21]. The stress-responding genes and their regulation pattern under drought were analyzed in common buckwheat cotyledons and roots [22] and female panicles in maize [23], and under salinity in roots and leaves of pomegranate [24].…”
Section: Drought and Salinitymentioning
confidence: 99%
“…The complex mechanism of drought tolerance in plants is regulated simultaneously by multiple genes [ 4 ]. RNA-seq offers an effective means to investigate plant resistance and has evolved into a potent tool for elucidating drought stress and predicting gene function [ 5 ]. Furthermore, transcriptome analysis can illuminate the molecular mechanisms involved in specific biological processes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%